Standardized Extubation and High Flow Nasal Cannula Training Program for Pediatric Critical Care Providers in Lima, Peru - Laura E. Ellington; Rosario Becerra Velásquez; José Tantaleán da Fieno; Gabriela Mallma Arrescurrenaga; Katie R. Nielsen (Association of American Medical Colleges, 2020)
Introduction Acute lower respiratory tract infections are the top cause of nonneonatal mortality in children under 5 years of age. Since many resource-limited settings lack basic pediatric respiratory support modalities, introducing respiratory technology in these settings may improve survival. Unfortunately, data suggest that many interventions in these settings are not sustainable and that after several months, local staff are no longer comfortable using newly implemented technology. Methods We aimed to create training modules for implementation of a standardized extubation process and high flow nasal cannula for physician and nurse providers at a tertiary care center in Lima, Peru. This training curriculum combined a didactic lecture with hands-on practicum and clinical case discussion over multiple sessions spanning a year. We created all materials in English and translated to Spanish for use. Participants completed evaluations after the training program to determine whether objectives were met. This training was intended for critical care providers but could be modified for other audiences. Results A total of 76 providers (12 attending/fellow critical care physicians, 40 bedside nurses, eight pediatric residents, and 14 medical technicians) participated in this multiday training. Almost all (75, 99%) participants felt the objectives were clearly stated, and 70 (92%) felt objectives were met. Discussion We have provided materials to help instructors set up and implement a standardized training curriculum with recommended timing and improvements based on feedback. The tools provided allow for adaptation depending on the instructors' primary objectives, language of audience (English or Spanish), and learners' level of training.